KEREN TANPA ROKOK DALAM RUMAH SEBAGAI GAYA HIDUP MASA KINI - Ade Saputra Nasution (Jurnal Abdimas Bina Bangsa, 2022)
Smoking activities in the house will have a negative impact on family members who participate in inhaling smoke from burned cigarettes or passive smokers. Passive smokers are much more likely to cause a disease than active smokers. This is very dangerous for family members, especially toddlers who are forced to inhale cigarette smoke inside the house. Therefore it is necessary to take a step to encourage the knowledge of housewives to prevent the risk of cigarette smoke in order to protect family health. Health promotion is a step that has been programmed in increasing public knowledge carried out by the government. The purpose of this community service is to increase knowledge and public awareness, especially for housewives in educating family members not to smoke in the house and protecting family members from the dangers of cigarette smoke. The method of service activities for housewives in RW 04 Cibogor that is carried out is health promotion regarding the danger signs of smoking and prevention. The result of this community service activity is that housewives have increased knowledge about the dangers and what they can do to prevent it